Privacy-Preserving Hypothesis Testing for Reduced Cancer Risk on Daily Physical Activity. - Kikuchi, Hiroaki; Huang, Xuping; Ikuji, Shigeta; Inoue, Manami (Journal of Medical Systems, 2018)
Privacy preserving data mining for medical information is an important issue to guarantee confidentiality of integrated multiple data sets. In this paper, we propose a secured scheme to estimate related risk of cancers accurately and effectively in a privacy-preserving way. We study models to configure the appropriate set of attributes to reduce risk of identity of an individual from being determined. We examine the proposed privacy preserving protocol for encrypted hypothesis test, using actual cohort data supplied by National Cancer Center.